An integrated mechanical and electrophysiological platform: towards multifunctional tissue-on-a-chip - Yu, Jing (Nanyang Technological University, 2023)
Cell culture in vitro platform is an indispensable tool for biology and is widely used in academic research and industrial practice in various fields ranging from fundamental biomolecule study to tissue engineering and regenerative medicine. Numerous engineering approaches are incorporated to optimize the culture condition and extend its capability. Besides commonly studied biochemical cues, mechanical and electrical aspects of cell properties are gaining popularity. DNA information alone is not sufficient for organ construction and these coordinated biological processes are highly dependent on extracellular factors. As living cells are actively interacting with the surrounding environment, the mechanical (mechanotransduction) and electrical feedback loops guide various cell functions. Nevertheless, the fundamental governing principles remain elusive and further studies are necessary to understand their driving mechanisms and relationships. Hence, this thesis hypothesizes that both mechanical and electrical feedback loops in cells correlate with intrinsic tissue properties and behaviours, and a tissue-on-a-chip device is proposed to establish a universal mechano-electrophysiological platform for cellular research in vitro with proper mechanobiological guidance. The topological effect, substrate stiffness, and electrical feedback from cells (MDCK cells and excitable myocytes) were investigated on the newly devised platform. Generally, the major findings in the thesis can be summarized from mechanical and electrical aspects. Firstly, cell culture was investigated from a mechanistic point of view. Topological confinement was imposed onto cell clusters and collective cell motion could be altered by different types of confinements. A fluid-to-solid transition was reported in the epithelial monolayer by reducing the confinement size, which may be attributed to varying surface tension. In addition to size, the shape of confinement also contributes significantly to collective cell motion. The prominent edge-amplification effect on circular islands weakened on square islands and disappeared on rectangular islands. These findings on fluid-to-solid transition could provide biological insights into the significance of topology in tissue development, cancer metastasis as well as wound healing. With the addition of electrical measurement, a new tissue-on-a-chip platform is devised, allowing real-time signal monitoring at physiologically relevant culture conditions. Both electrical signals and mechanical signals were successfully collected and drug responses of myocytes cultured on different substrates gave rise to distinctive results, which highlights the importance of physiological stiffness during testing. Myocytes on the 10 kPa substrate matured faster than myocytes on rigid substrates and probably had a higher level of protein expression on the cell membrane, thereby leading to a more active drug response. In this thesis, the importance of a physiologically relevant testing platform is demonstrated, and the capability of mechanical and electrophysiological measurements is reported. While the mechanical and electrical factors contribute greatly to cell behaviour individually, these factors are also intercorrelated and work synergistically. This platform provides more reliable data as compared to the conventional rigid platform and is promising in the study of mechanical, electrical and coupling effects from a cellular perspective. Bridging the gap between biology and electrophysiology testing will be a critical field of research in the future, in favour of truly reliable data.